Collaborative Governance In Road Infrastructure Development In Gununghalu Sub-District, West Bandung District - Ria Anjani; Wirman Syafri; Yudi Rusfiana (Sean Institute, 2024)
The concept of collaborative governance is now a view in government administration, sharing roles with the community and the private sector is a change that makes all sectors stand equal and democratic. This does not only apply to the central government, but also regional governments, including West Bandung Regency. This region is actively implementing accelerated development, especially in the field of road infrastructure. The aim of this research is to analyze the application of the concept of collaborative governance in the development of road infrastructure in Gununghalu District, West Bandung Regency. The research design used is descriptive analysis using survey studies as the management and a qualitative approach. Observation and interviews are techniques used to collect supporting and inhibiting factors as the required data. The results obtained from this research are the success of collaborative governance in the road infrastructure project due to supportive initial conditions, facilitative leadership, institutions that have been formed, collaboration between actors that runs smoothly, with the supporting factors of cooperation and close interaction between stakeholders being built. with the principle of transparency, the concept of collaborative governance can work well